Compatibility Between Platelet Histogram with IP Message and Platelet Morphology in Thrombocytopenia Patients - Dewa Ayu Puja Satya Dinarta; Anik Handayati; Syamsul Arifin; Patcharanee Pavadhgul (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
The aim of this study was to evaluate the compatibility of platelet histogram results with IP Message on the hematology analyzer Sysmex XN-1000 for the platelet morphology of peripheral blood smears of thrombocytopenia patients. This was a quantitative descriptive study of 54 samples taken using the saturation sampling technique at Grati Pasuruan Hospital from April 1–30 2023. The results showed that the histograms that often appeared were abnormal heights on the PU Flag and the IP Messages that often appeared were “PLT Clumps?”, “PLT Abn Distribution”, and “Thrombocytopenia”, with a compatibility level of platelet morphology on peripheral blood smear examination reaching 90.7%. The study concluded that there was a high compatibility between the platelet histogram results accompanied by the IP Message and the platelet morphology of the peripheral blood smear of thrombocytopenia patients, which could improve the accuracy and efficiency of platelet count examination.